(untitled) (Communications in Computational Chemistry, 2025)
Ammonia has been proposed as a potential carbon-free energy source. However, a highly active catalyst is required for ammonia oxidation to promote the combustion rate. In this study, the single-atom copper catalyst loaded on the reconstructed cerium dioxide (100) surface with the pocket-like structure (Cu_1/CeO_4-t-p) is constructed for ammonia oxidation, and the catalytic process is investigated using the density functional theory calculations corrected by on-site Coulomb interactions (DFT+U). The adsorptions of ammonia and oxygen, the dissociation of ammonia and the oxidation of the dissociated ammonia species are systematically examined.